Characterization of Ccw12p, a major key player in cell wall stability of Saccharomyces cerevisiae - Ragni, Enrico; Sipiczki, Matthias; Strahl, Sabine (Yeast, 2007)
The GPI-anchored mannoprotein Ccw12p is a crucial structural component of the cell wall of Saccharomyces cerevisiae. Compared to wild-type, the mutant ccw12Δ grows more slowly, is highly sensitive to Calcofluor white and contains 2.5 times more cell wall chitin. In this study, electron microscopy of ccw12Δ cell walls revealed that, with respect to wild-type, the inner glucan layer is thicker with irregular depositions of wall material, whereas the outer mannan layer is less condensed. Biochemical analyses of cell wall glucan suggest that in the absence of Ccw12p, GPI-anchored cell wall proteins are transferred preferentially to chitin and random deposition of cell wall material reinforces the inner glucan-chitin layer, thereby enhancing the overall stability of the cell wall. To further elucidate the role of Ccw12p, structure-function analysis was performed. We demonstrate that Ccw12p is highly N-glycosylated. However, loss of N-glycans does not affect Ccw12p functionality. In contrast, deletion of the repeated amino acid motive TTEAPKNGTSTAAP in the C-terminal part of the protein affects Ccw12p function. Copyright © 2007 John Wiley & Sons, Ltd.